The utility of the MMPI-2-RF to predict the outcome of a smoking-cessation treatment. (1st February 2017) - Martínez, Úrsula; Fernández del Río, Elena; López-Durán, Ana; Becoña, Elisardo
Abstract: People with psychopathology experience high rates of smoking and have more trouble quitting. The Minnesota Multiphasic Personality Inventory-2 Restructured Form (MMPI-2-RF; Tellegen & Ben-Porath, 2008, 2009) is a valid and reliable instrument for the assessment of psychopathology. In this study, we examined the ability of the MMPI-2-RF to assess psychopathology and to predict smoking cessation outcomes in a sample of 281 smokers seeking psychological treatment to stop smoking at the end of treatment and at 6- and 12-month follow-ups. Results showed that T -scores < 65 on Disaffiliativeness (DSF) scale were associated with a higher likelihood of smoking at the end of treatment, and T- scores ≥ 65 on Neurological Complaints (NUC) scale were associated with a higher likelihood of smoking at the 12-month follow-up, after controlling for the effect of age and initial levels of nicotine dependence. The results highlight the usefulness of the MMPI-2-RF in the field of smoking cessation treatment. Highlights: Psychopathology influences smoking cessation treatment. The MMPI-2-RF is a valid and reliable instrument to assess phychopathology. The scales of the MMPI-2-RF are used to predict smoking in smokers seeking treatment. DSF and NUC scales predict smoking at the end of treatment and after 12 months.